Fiction, friction and fracture : autobiographic novels as a site for changing discouses [i.e. discourses] around subjectivity, truth and identity - Lombard, Sunell (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil)--Stellenbosch University, 2008.